2017
DOI: 10.1093/ejcts/ezx324
|View full text |Cite|
|
Sign up to set email alerts
|

2017 ESC/EACTS Guidelines for the management of valvular heart disease

Abstract: The content of these European Society of Cardiology (ESC) Guidelines has been published for personal and educational use only. No commercial use is authorized. No part of the ESC Guidelines may be translated or reproduced in any form without written permission from the ESC. Permission can be obtained upon submission of a written request to Oxford University Press, the publisher of the European Heart Journal and the party authorized to handle such permissions on behalf of the ESC (journals.permissions@oxfordjou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
174
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 513 publications
(188 citation statements)
references
References 208 publications
(21 reference statements)
2
174
0
12
Order By: Relevance
“…Mean pressure gradients and peak flow velocity obtained from numerical simulations are shown; values in brackets correspond to the boundaries for ranges of the stenosis severity presented in Guidelines …”
Section: Resultsmentioning
confidence: 99%
“…Mean pressure gradients and peak flow velocity obtained from numerical simulations are shown; values in brackets correspond to the boundaries for ranges of the stenosis severity presented in Guidelines …”
Section: Resultsmentioning
confidence: 99%
“…However, the major clinical diagnoses of the patients could also be collected in the echocardiography database at our center and were rechecked by the echocardiography reports. Forth, the recent ESC/EACTS guidelines [29] stress the importance of tricuspid disease especially in patients with significant mitral valve disease, and the time for intervention of TR should be considered early. Our research found that severe TR patients with left-sided valve surgery have a better prognosis than those who did not accept left-sided valve surgery, which demonstrates the benefits of left-sided valve intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This is already reflected in the 2017 ESC/EACTS Valvular Heart Disease Guidelines in which age >75 alone is considered in the list of factors favouring TAVI if transfemoral access is possible 39. However, in patients with greater life expectancy, TAVI durability is still an unanswered question requiring further follow-up.…”
Section: What Are the Remaining Challenges For Tavi In Low-risk Patiementioning
confidence: 99%